Two new species and new records of Psychoda Latreille (Diptera: Psychodidae: Psychodinae) from Brazil, with comments on supraspecific classification of the genus - Bravo, Freddy; Cordeiro, Danilo; Chagas, Cinthia (Zootaxa, 2006)
Two new species of Brazilian Psychoda Latreille are described, and Psychoda alternata Say and P. zetoscota Quate are recorded for the first time from Brazil. Psychoda divaricata Duckhouse, already described from southern Brazil, was recorded in the northeastern part of that country, as well as in the eastern Amazon region. The supraspecific classification proposed for the species of Psychoda according to Quate (= Psychodini of Jeñek) are discussed. A new classification is suggested that considers only one genus, Psychoda, divided into 12 subgenera: subgenus Psychoda Latreille, subgenus Copropsychoda Vaillant, subgenus Falsologima Jeñek & Harten, subgenus Psychodula Jeñek, subgenus Psychomora Jeñek, subgenus Psychana Jeñek & Harten, subgenus Logima Eaton, subgenus Tinearia Schellenberg, subgenus Chodopsycha Jeñek, subgenus Ypsydocha Jeñek, subgenus Psychodocha Jeñek, and subgenus Psycha Jeñek. A list of the Psychoda species from Latin America and the Caribbean region is presented.